2019
DOI: 10.1038/s41559-018-0769-y
|View full text |Cite
|
Sign up to set email alerts
|

A systems approach reveals urban pollinator hotspots and conservation opportunities

Abstract: Urban areas are often perceived to have lower biodiversity than the wider countryside, but a few small-scale studies suggest that some urban land uses can support substantial pollinator populations. We present a large-scale, well-replicated study of floral resources and pollinators in 360 sites incorporating all major land uses in four British cities. Using a systems approach, we developed Bayesian network models integrating pollinator dispersal and resource switching to estimate city-scale effects of manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
319
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 342 publications
(346 citation statements)
references
References 50 publications
8
319
3
Order By: Relevance
“…To the contrary, prior studies in this system found that urban land use was negatively associated with colony productivity (Sponsler and Johnson 2015) and that honey bees situated at the agricultural-suburban divide of site CC dedicated significantly more foraging activity toward rural agricultural landcover components (Sponsler et al 2017). While Ohio urban landcover apparently contains a diverse floral assemblage, a trait which likely makes it amenable to generalist solitary bees and bumble bees (Samuelson et al 2018, Baldock et al 2019, it may be depauperate in the high-volume floral resource patches which drive honey bee colony growth. Thus, future research contributions which seek to explicitly characterize the nutritional currency value of honey bee forage diversity may benefit from considering the implications of urban landscapes through the lens of optimal foraging theory and the life history of the honey bee.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…To the contrary, prior studies in this system found that urban land use was negatively associated with colony productivity (Sponsler and Johnson 2015) and that honey bees situated at the agricultural-suburban divide of site CC dedicated significantly more foraging activity toward rural agricultural landcover components (Sponsler et al 2017). While Ohio urban landcover apparently contains a diverse floral assemblage, a trait which likely makes it amenable to generalist solitary bees and bumble bees (Samuelson et al 2018, Baldock et al 2019, it may be depauperate in the high-volume floral resource patches which drive honey bee colony growth. Thus, future research contributions which seek to explicitly characterize the nutritional currency value of honey bee forage diversity may benefit from considering the implications of urban landscapes through the lens of optimal foraging theory and the life history of the honey bee.…”
Section: Discussionmentioning
confidence: 91%
“…Understanding how alterations in landscape structure and composition affect the composition and functioning of communities is a central goal in applied ecology. Nutritional limitation is likely a bottom-up factor involved in shaping biological communities, especially with respect to pollinators (Samuelson et al 2018, Baldock et al 2019, Wood et al 2019). Thus, a greater understanding of pollinator landscape and nutritional ecology is central to improving pollinator health.…”
Section: Discussionmentioning
confidence: 99%
“…The two simplest possible explanations might be that, firstly, the treated sites became progressively less attractive to foraging pollinators which emigrated even when resources they were using were still available, because pollinators are attracted by total flowering plant richness and abundance (e.g. 47 ). Another possible explanation is that plant removal made the network structure became more fragile, so that species would became less anchored to other species in the interaction web and more exposed to extinction 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…Body size correlates with the foraging range of flower‐visiting Hymenoptera (Greenleaf et al ); this finding was extended to flower‐visiting Diptera, Lepidoptera and Coleoptera to estimate insects’ mobility (Baldock et al ). Using the same approach, we measured the intertegular distance for Hymenoptera, Diptera and Lepidoptera; for Coleoptera, we measured the length of the elytra and width at the widest point.…”
Section: Methodsmentioning
confidence: 97%